Taxes 101 : from understanding forms and filing to using tax laws and policies to minimize costs and maximize wealth, an essential primer on the US tax system - Cagan, Michele (Adams 101., 2024)
"If you want to understand your finances, you need to understand your taxes. Learn everything you need to know about the US tax system and become more financially independent with Taxes 101. As people become more motivated to be as financially literate as possible, understanding every part of their financial wellness is key. With Taxes 101, you will learn the basics of the US tax system, from the system structure and kinds of taxes to all the tax laws that lead to deductions and credits and the forms associated with filing. This all-in-one financial resource lays the foundation with basic information about the tax system so you can make better choices about your financial wellness"--